Probing the druggability of membrane-bound Rab5 by molecular dynamics simulations - Eileen Edler; Matthias Stein (Taylor & Francis Group, 2017)
Rab5 is a small GTPase and a key regulator in early endosomal trafficking. Rab5 and its effectors are involved in a large number of infectious diseases and certain types of cancer. We performed µs atomistic molecular dynamics simulations of inactive and active full-length Rab5 anchored to a complex model bilayer with composition of the early endosome membrane. Direct interactions between the Rab5 G domain and the bilayer were observed. We found two dominant nucleotide-dependent orientations characterised by a different accessibility of the switch regions. The "buried switch" orientation was mainly associated with inactive Rab5 accompanied with a rather extended structure of the hypervariable C-terminal region. Active Rab5 preferred an orientation in which the switch regions are accessible to effector proteins. These structural differences may provide an opportunity to selectively target one Rab5 state and lead to new approaches in the development of Rab5-specific therapies.